Hot rolling roll outer layer material and, producing method thereof as well as hot rolling composite roll
The hot rolling outer layer material with a tailored composition and microstructure, combined with a rapid pouring process, addresses the insufficient wear resistance of existing rolls while maintaining seizure and crack resistance, resulting in improved roll life and productivity.
Patent Information
- Application Number
- JP2024099315
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-06-20
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2044-06-20
AI Technical Summary
Existing hot rolling rolls lack sufficient wear resistance while maintaining seizure and crack resistance, necessitating a new approach beyond the conventional extension of carbide generation.
A hot rolling outer layer material with a specific composition and microstructure, including a graphite area ratio of 0.5 to 6.0%, cementite area ratio of 30 to 55%, and MC-type carbide area ratio of 0.1 to 5.0%, along with a rapid molten metal pouring process within three minutes after component adjustment, to enhance wear resistance and maintain seizure and crack resistance.
The solution achieves remarkable wear resistance while maintaining excellent seizure and crack resistance, thereby improving roll life and productivity in hot rolling.
Smart Images

Figure 2025058885000003 
Figure 2025058885000004 
Figure 2025058885000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a hot rolling roll outer layer material, a manufacturing method thereof, and a hot rolling composite roll. The hot rolling roll outer layer material of the present invention is particularly suitable as an outer layer material for a work roll of a hot rolling mill for steel sheets, and the hot rolling composite roll of the present invention is particularly suitable as a work roll of a hot rolling mill for steel sheets. [Background technology]
[0002] In recent years, the environment in which rolls are used has become harsher with the progress of hot rolling technology for steel sheets, and the production volume of steel sheets that are subject to a large rolling load, such as high-strength steel sheets and thin-walled products, is also increasing. For this reason, the quality level required for rolling work rolls is increasing, and high-performance rolling work rolls are being demanded.
[0003] In the rear stands of hot finishing mills, work rolls with outer layers made of grain-based cast iron or high-alloy grain-based cast iron, which have excellent accident resistance, are used. One type of rolling accident that can occur in the rear stands of hot finishing mills is the squeezing accident.
[0004] A rolling accident is a phenomenon in which the ends of the rolled material are folded over and caught between the rolls. When a rolling accident occurs, the rolled material seizes on the roll surface, and a large thermal and mechanical load is generated on the roll, which may cause cracks on the roll surface. Such cracks may be 1 mm deep or more, and when such cracks occur, the roll surface must be ground to remove the cracks, which increases the work cost and shortens the life of the roll. Therefore, there is a demand for hot rolling work rolls with excellent seizure and crack resistance, which prevent the steel plate from seizing and cracks from occurring and progressing even if a rolling accident occurs.
[0005] As an outer layer material for a hot rolling roll or a hot rolling roll, for example, Patent Document 1 proposes an outer layer material for a rolling roll, which contains, by mass%, C: more than 3.0% and 4.0% or less, Si: 3.0% or less, Ni: 2.3 to 5.5%, Cr: 1.0 to 2.0%, V: 0.3 to 10.0%, Ti: 0.01 to 2.0%, the balance being Fe and impurity elements, has graphite and MC-based carbides in the metal structure, and has a graphite spheroidization rate of 0.5 or more. Patent Document 1 states that by making the shape of the graphite finely spherical and dispersing the graphite uniformly in the metal structure, the wear resistance, surface roughening resistance, and accident resistance of the outer layer material are improved.
[0006] Patent Document 2 proposes a composite roll for rolling, which contains, by mass%, C: 3.0-4.5%, Si: more than 0% and not more than 2.0%, Mn: more than 0% and not more than 1.5%, Ni: 3.0-5.0%, Cr: 1.4-4.0%, Mo: 0.1-1.5%, V: more than 0% and not more than 3.0%, with the balance being Fe and unavoidable impurity elements, C, Si, and Cr being 4.0%≦C+Si / 3+Cr / 7.5≦5.5%, and the metal structure of the peripheral surface used for rolling the outer layer has an area ratio of cementite of 40% or more and less than 46%. Patent Document 2 states that since a large amount of hard cementite is present, the composite roll for rolling has excellent wear resistance and surface roughening resistance.
[0007] Patent Document 3 proposes a composite roll for rolling in which the metal structure of the peripheral surface used for rolling has an area ratio of cementite of 40 to 60% and an area ratio of graphite of 0.5 to 2.0%. Patent Document 3 claims that a large amount of hard cementite is crystallized and the graphite area ratio is adjusted, resulting in a composite roll for rolling with excellent wear resistance, surface roughening resistance, and crack resistance.
[0008] Patent Document 4 proposes a composite roll for rolling, which contains, in mass%, C: 2.2-3.2%, Si: 1.0-3.0%, Mn: 0.3-2.0%, Ni: 3.0-7.0%, Cr: 0.5-2.5%, Mo: 1.0-3.0%, V: 2.5-5.0%, Nb: more than 0% but not more than 0.5%, the balance being Fe and unavoidable impurities, Nb and V being Nb / V<0.1, and C, Si, Cr, Mo, V, and Nb being 2.1×C+1.2×Si-Cr+0.5×Mo+(V+Nb / 2)≦13.0%. Patent Document 4 claims that satisfying the two relational expressions results in a composite roll for rolling with excellent crack resistance and wear resistance.
[0009] Patent Document 5 proposes a centrifugally cast composite roll for rolling, which contains, by mass%, C: 1.5-3.5%, Si: 0.3-3.0%, Mn: 0.1-3.0%, Ni: 1.0-6.0%, Cr: 1.5-6.0%, Mo: 0.1-2.5%, V: 2.0-6.0%, Nb: 0.1-3.0%, B: 0.001-0.2%, N: 0.005-0.070%, with the balance being Fe and unavoidable impurities, in which Ni, Cr, and Mo satisfy 2×Ni+0.5×Cr+Mo>10.0, the outer layer Shore hardness A of the roll surface is Hs75≦A≦Hs85, and the residual stress B of the roll surface is 100MPa≦B≦350MPa. Patent Document 5 describes that a composite roll for rolling having excellent wear resistance and crack resistance can be obtained by having a predetermined component composition and setting the Shore hardness of the outer layer of the roll surface within a predetermined range. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2005-177808 A [Patent Document 2] JP 2018-75638 A [Patent Document 3] JP 2015-193025 A [Patent Document 4] JP 2018-118319 A [Patent Document 5] International Publication No. 2020 / 203570 Summary of the Invention [Problem to be solved by the invention]
[0011] In addition to improving the seizure resistance, hot rolling rolls with better wear resistance are required in recent years from the viewpoint of improving the roll consumption rate and improving the roll life. However, the outer layer materials of hot rolling rolls and hot rolling rolls proposed in Patent Documents 1 to 5 are not sufficiently wear-resistant and there is room for improvement. In the techniques of these patent documents, wear resistance is improved by generating a large amount of carbides (cementite, MC type carbides). However, in order to further improve wear resistance while maintaining seizure resistance, a new perspective that is not an extension of conventional techniques is required.
[0012] The present invention has been made in consideration of the above circumstances, and has an object to provide an outer layer material for a hot rolling roll which is extremely excellent in wear resistance, and also has good resistance to seizure and cracking. [Means for solving the problem]
[0013] Hot rolling rolls with grain cast iron or high alloy grain cast iron as the outer layer material form graphite in the metal structure, which makes the rolled material less likely to seize even in the event of a squeezing accident, and suppresses the occurrence and progression of cracks. However, because graphite is soft, if the amount of graphite formed in the metal structure of the outer layer material increases, there is a problem that the wear resistance of the roll outer layer material decreases.
[0014] In the conventional technology, wear resistance has been improved by generating a predetermined amount of MC type carbides and / or cementite, but further improvement of wear resistance has been difficult by increasing the amount of these carbides, which is an extension of the conventional approach. Moreover, an excessive increase in the amount of carbides may cause a decrease in crack resistance. In order to solve such problems, the present inventors conducted extensive research and obtained the following findings (1) to (3).
[0015] (1) The contents of predetermined elements must be within predetermined ranges, and the ratio of the Mn content to the Ni content (Mn / Ni) must be 0.20 to 0.80. (2) When manufacturing an outer layer material for a hot rolling roll, the time from the completion of the composition adjustment of the molten metal having the composition of the outer layer material (molten metal for forming the outer layer material) to the start of pouring the molten metal for forming the outer layer material into the mold must be within 3 minutes. (3) It is preferable that the metal structure has an area ratio of graphite of 0.5 to 6.0%, an area ratio of cementite of 30 to 55%, and an area ratio of MC type carbide of 0.1 to 5.0%.
[0016] The present invention was completed based on the above findings and further studies, and the gist of the present invention is as follows. [1] In mass percent, C: 2.50-4.00%, Si: 0.60-2.50%, Mn: 0.50-4.00%, Cr: 0.50~3.50%, Ni: 1.50-4.40%, V: 1.00~2.50%, Nb: 0.10-0.75%, and Mo: 0.30 to 1.50% and the balance being Fe and unavoidable impurities; A roll outer layer material for hot rolling, the Mn and Ni contents of which satisfy the following formula (1), and the Si and V contents of which satisfy the following formula (2): 0.20≦Mn / Ni≦0.80 (1) 0.55≦Si / V≦1.85 (2) Here, each element symbol in formulas (1) and (2) indicates the content (mass %) of the corresponding element. [2] The composition further includes, in mass%, W: 2.0% or less, Co: 1.00% or less, B: 0.1000% or less, Ti: 0.30% or less, and The hot rolling roll outer layer material according to [1], containing one or more selected from the following: Zr: 0.30% or less. [3] The hot rolling roll outer layer material according to [1] or [2], having a metal structure in which the area ratio of graphite is 0.5 to 6.0%, the area ratio of cementite is 30 to 55%, the area ratio of MC type carbides is 0.1 to 5.0%, and the average crystal grain size of martensite and bainite is 2.0 to 20.0 μm. [4] A method for producing an outer layer material for hot rolling roll according to any one of [1] to [3], A method for producing an outer layer material for a hot rolling roll, comprising the steps of: starting to pour the molten metal for forming the outer layer material into a mold within 3 minutes after completing the composition adjustment of the molten metal for forming the outer layer material. [5] A composite roll for hot rolling having a three-layer structure of an outer layer, an intermediate layer, and an inner layer, or a two-layer structure of an outer layer and an inner layer, The outer layer of a hot rolling composite roll is made of the outer layer material for a hot rolling roll according to any one of [1] to [3]. Effect of the Invention
[0017] According to the present invention, it is possible to obtain an outer layer material for a hot rolling roll which is extremely excellent in wear resistance, and also has good resistance to seizure and cracking. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic diagram showing the positions at which test pieces for observing the outer surface were taken from a hot rolling roll outer layer material (sleeve roll). [Diagram 2] FIG. 2 is a schematic diagram showing the positions at which wear test pieces were taken from the sleeve roll. [Diagram 3] FIG. 3 is a diagram showing a schematic configuration of a testing machine used in the wear test. [Figure 4] FIG. 4 is a diagram showing a schematic configuration of a test machine used in the seizure test. [Diagram 5] FIG. 5 is a schematic diagram showing the positions at which test pieces (seizure test pieces) were taken from the sleeve roll. [Figure 6]FIG. 6 is a diagram showing a schematic diagram of a method for evaluating the seizure area ratio of a seizure test piece. [Figure 7] FIG. 7 is a schematic diagram showing the position where a test piece (thermal shock test piece) was taken from a sleeve roll, and a diagram showing a method for evaluating the crack depth. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] First, the reason for limiting the component composition of the hot rolling roll outer layer material (outer layer of the hot rolling composite roll) of the present invention will be described. Note that, hereinafter, % indicating the content of each component means mass % unless otherwise specified.
[0020] C: 2.50-4.00% C increases the hardness of the matrix (martensite and / or bainite) and also forms hard carbides by bonding with elements such as Fe, V, Cr, and Mo, thereby contributing to the improvement of wear resistance. Furthermore, C is an element that crystallizes as graphite in the metal structure due to graphitization-promoting elements such as Si and Ni, and also improves seizure resistance. If the C content is less than 2.50%, the amount of carbides and graphite is insufficient, and therefore wear resistance and seizure resistance are reduced. On the other hand, if the C content exceeds 4.00%, the carbides become coarse and the crack resistance is reduced. For this reason, the C content is limited to 2.50 to 4.00%. The C content is preferably 2.70% or more, more preferably 2.80% or more. The C content is preferably 3.80% or less, more preferably 3.60% or less.
[0021] Silicon: 0.60 to 2.50% Si acts as a deoxidizer and is an element that improves the castability of the molten metal. In addition, Si is an element that promotes graphitization and has the effect of crystallizing C as graphite. In order to obtain such an effect, the Si content must be 0.60% or more. On the other hand, if the Si content exceeds 2.50%, the matrix structure becomes embrittled and the wear resistance decreases. For this reason, the Si content is limited to 0.60 to 2.50%. The Si content is preferably 0.70% or more, and more preferably 0.90% or more. The Si content is preferably 2.30% or less, and more preferably 2.10% or less.
[0022] Mn: 0.50-4.00% Mn is an element that fixes S as MnS and renders S harmless, and also has the effect of improving hardenability and strengthening the matrix (solid solution strengthening) by partially dissolving in the matrix structure. In order to obtain such an effect, it is necessary to contain 0.50% or more of Mn. On the other hand, even if the Mn content exceeds 4.00%, the effect is saturated and the effect commensurate with the content cannot be expected, and furthermore, the material may become embrittled. For this reason, the Mn content is limited to 0.50 to 4.00%. The Mn content is preferably 0.70% or more, more preferably 0.90% or more, and even more preferably more than 1.00%. The Mn content is preferably 3.80% or less, more preferably 3.60% or less.
[0023] Cr: 0.50~3.50% Cr combines with C to form a solid solution in cementite and / or Cr-based carbides (M7C3, M 23C6, etc.), and further improves the hardenability of the matrix to make the matrix martensite and / or bainite, thereby improving the wear resistance. In order to obtain such an effect, a Cr content of 0.50% or more is required. On the other hand, a Cr content exceeding 3.50% is not preferable because it increases coarse Cr-based carbides, which may reduce the crack resistance. For this reason, the Cr content is limited to 0.50 to 3.50%. The Cr content is preferably 0.70% or more, more preferably 0.80% or more. The Cr content is preferably 3.30% or less, more preferably 3.10% or less.
[0024] Ni: 1.50~4.40% Ni is an element that dissolves in the matrix, lowers the transformation temperature of austenite during heat treatment, improves the hardenability of the matrix, and transforms the matrix into martensite and / or bainite, thereby improving wear resistance. Ni is also an element that promotes graphitization, increases the amount of graphite produced, and improves seizure resistance. If the Ni content is less than 1.50%, these effects become insufficient. Therefore, the Ni content is set to 1.50% or more. On the other hand, if the Ni content exceeds 4.40%, the austenite transformation temperature becomes too low, and austenite remains even after heat treatment, thereby reducing wear resistance. Therefore, the Ni content is limited to 1.50 to 4.40%. The Ni content is preferably 1.70% or more, more preferably 1.90% or more. The Ni content is preferably 4.30% or less, more preferably 4.10% or less.
[0025] V: 1.00~2.50% V is an element that forms extremely hard V-based carbides (MC type carbides) and improves wear resistance. Such an effect is obtained with a V content of 1.00% or more. On the other hand, a V content of more than 2.50% coarsens the MC type carbides and further reduces the amount of graphite produced, thereby reducing the seizure resistance. For this reason, the V content is limited to 1.00 to 2.50%. The V content is preferably 1.10% or more, and more preferably 1.30% or more. The V content is preferably 2.40% or less, and more preferably 2.30% or less.
[0026] Nb: 0.10-0.75% Nb is an element that improves wear resistance through the effect of strengthening the MC carbide by dissolving in the MC carbide and increasing the fracture resistance of the MC carbide. Nb also has the effect of suppressing segregation of the MC carbide during centrifugal casting. Such an effect becomes remarkable when the Nb content is 0.10% or more. On the other hand, when the Nb content exceeds 0.75%, coarse MC carbides are generated and the seizure resistance is reduced. For this reason, the Nb content is limited to 0.10 to 0.75%. The Nb content is preferably 0.15% or more, more preferably 0.20% or more, and the Nb content is preferably 0.70% or less, more preferably 0.65% or less.
[0027] Mo: 0.30-1.50% Mo is an element that combines with C to form a solid solution in cementite and / or M2C type carbides, thereby improving wear resistance. Mo also dissolves in hard MC type carbides in which V, Nb and C are combined, strengthening the carbides. Through such action, Mo improves the wear resistance of the roll outer layer material. In order to obtain such an effect, it is necessary to contain Mo at 0.30% or more. On the other hand, if the Mo content exceeds 1.50%, coarse Mo-based carbides are generated, lowering the crack resistance. For this reason, the Mo content is limited to 0.30 to 1.50%. The Mo content is preferably 0.40% or more, more preferably 0.50% or more. The Mo content is preferably 1.40% or less, more preferably 1.30% or less.
[0028] The balance other than the above components can be Fe and unavoidable impurities. Examples of unavoidable impurities include Al, S, P, Sb, Mg, Cu, N, O, and Sn. These are mixed in from the raw materials or refractories during melting of the raw materials. These unavoidable impurities are preferably Al: 0.1% or less, S: 0.05% or less, P: 0.1% or less, Sb: 0.2% or less, Mg: 0.1% or less, Cu: 0.1% or less, N: 0.1% or less, O: 0.05% or less, and Sn: 0.1% or less.
[0029] The outer layer material for a hot rolling roll of the present invention may optionally contain, in addition to the above-mentioned component composition, one or more selected from the following:
[0030] W: 2.0% or less W is an element that dissolves in the matrix, strengthens the matrix, and improves wear resistance, and dissolves in cementite to improve wear resistance. However, if W is contained in an amount exceeding 2.0%, not only will the effect be saturated, but coarse M2C or M6C carbides will be formed, lowering crack resistance. For this reason, when W is contained, the W content is limited to a range of 2.0% or less. The W content is preferably 1.8% or less, and more preferably 1.6% or less. When W is contained, in order to obtain the above effect, the W content is preferably 0.1% or more, and more preferably 0.4% or more.
[0031] Co: 1.00% or less Co is an element that dissolves in the matrix, strengthens the matrix, and improves wear resistance. However, if the Co content exceeds 1.00%, the effect is saturated and the effect commensurate with the content cannot be expected, which is economically disadvantageous, and the matrix structure may become embrittled, resulting in a decrease in wear resistance. For this reason, when Co is contained, the Co content is limited to a range of 1.00% or less. The Co content is preferably 0.80% or less. When Co is contained, in order to obtain the above-mentioned effect of improving wear resistance, the Co content is preferably 0.05% or more, and more preferably 0.10% or more.
[0032] B: 0.1000% or less B is an element that improves the hardenability of the matrix, converts the matrix into martensite and / or bainite, and improves wear resistance. However, a B content of more than 0.1000% is not preferable because brittle borocarbides are formed and wear resistance is reduced. Therefore, when B is contained, the B content is limited to a range of 0.1000% or less. The B content is preferably 0.0500% or less. When B is contained, in order to obtain the effect of improving wear resistance, the B content is preferably 0.0010% or more, and more preferably 0.0020% or more.
[0033] Ti: 0.30% or less, Zr: 0.30% or less Ti and Zr are elements that combine with C to form carbides and improve wear resistance. However, if the Ti and Zr contents exceed 0.30%, respectively, the morphology of cementite is changed and wear resistance is reduced. Therefore, when Ti and Zr are contained, the Ti and Zr contents are limited to a range of 0.30% or less. The Ti and Zr contents are preferably 0.20% or less, respectively. When Ti and Zr are contained, in order to obtain the effect of improving wear resistance, the Ti and Zr contents are preferably 0.01% or more, and more preferably 0.05% or more, respectively.
[0034] Furthermore, in the present invention, in order to obtain a hot rolling roll outer layer material having significantly improved wear resistance and also good seizure resistance and crack resistance, it is necessary that the contents of Mn and Ni satisfy the following formula (1), and that the contents of Si and V satisfy the following formula (2). 0.20≦Mn / Ni≦0.80 (1) 0.55≦Si / V≦1.85 (2) Here, the element symbols Mn and Ni in formula (1) represent the Mn content (mass%) and Ni content (mass%), respectively, and the element symbols Si and V in formula (2) represent the Si content (mass%) and V content (mass%), respectively.
[0035] If Mn / Ni is less than 0.20, sufficient wear resistance improvement effect cannot be obtained. On the other hand, if Mn / Ni is more than 0.80, the amount of graphite generated is insufficient, and seizure resistance is reduced. Mn / Ni is preferably 0.30 or more, more preferably 0.35 or more. Also, Mn / Ni is preferably 0.70 or less, more preferably 0.65 or less.
[0036] If the Si / V ratio is less than 0.55, the amount of graphite produced is small, and seizure resistance may decrease. On the other hand, if the Si / V ratio is more than 1.85, the amount of MC carbides is insufficient, and wear resistance may decrease. The Si / V ratio is preferably 0.60 or more, and more preferably 0.70 or more. The Si / V ratio is preferably 1.70 or less, and more preferably 1.65 or less.
[0037] The outer layer material for hot rolling rolls of the present invention has a metal structure containing a matrix, graphite, cementite, and MC type carbides. Graphite is an important element that contributes to seizure resistance by suppressing or reducing the seizure of the rolled material onto the roll surface when a drawing accident occurs, and furthermore, graphite present inside the roll contributes to crack resistance by suppressing the progress of cracks. In addition, cementite and MC type carbides are important elements for ensuring wear resistance, and in the present invention, the contents of Mn and Ni satisfy formula (1), thereby strengthening the matrix (martensite and / or bainite), and contributing to a significant improvement in wear resistance.
[0038] In the metal structure of the outer layer material for hot rolling roll of the present invention, the matrix is martensite and / or bainite. In order to obtain good crack resistance, it is preferable to perform heat treatment (tempering) after the formation of martensite and / or bainite. The area ratio of graphite is preferably 0.5 to 6.0%, more preferably 0.7 to 5.5%. The area ratio of cementite is preferably 30 to 55%, more preferably 35 to 50%. The area ratio of MC type carbide is preferably 0.1 to 5.0%, more preferably 0.3 to 4.5%. The remainder other than the above includes one or more of pearlite, retained austenite, M2C type carbide, and M6C type carbide. The area ratio of the remainder is preferably 0.1 to 15%, more preferably 1.0 to 10%. The average grain size of martensite and bainite constituting the matrix is preferably 2.0 to 20.0 μm, more preferably 3.5 to 18.5 μm. Such an average grain size can be obtained by limiting the time from the completion of the composition adjustment of the molten metal for forming the outer layer material to the start of pouring the molten metal into the mold, which will be described later. That is, by setting the time from the completion of the composition adjustment of the molten metal for forming the outer layer material to the start of pouring the molten metal into the mold within 3 minutes, graphite is generated at an area ratio of 0.5 to 6.0% when the molten metal solidifies, and martensite and / or bainite with an average grain size of 2.0 to 20.0 μm is generated in the matrix during the subsequent cooling process. On the other hand, if the time from the completion of the composition adjustment of the molten metal for forming the outer layer material to the start of pouring the molten metal into the mold exceeds 3 minutes, the amount of graphite generated when the molten metal solidifies decreases, and the amount of C dissolved in the matrix increases. As a result, the average grain size of martensite and / or bainite does not satisfy the range of 2.0 to 20.0 μm.
[0039] The method for measuring the graphite area ratio is not particularly limited, but in the present invention, the graphite area ratio was measured by the following method. A test piece for observing the outer surface was taken from the outer layer material of a hot rolling roll, and the observation surface was mirror-polished, and then metallographic photographs of five visual fields were taken at 100x magnification. The graphite area ratio was measured by image analysis based on the obtained metallographic photograph, and the average value of the five visual fields was calculated to be the graphite area ratio of the test piece. More specifically, the graphite area ratio was measured by the method described in the Examples.
[0040] The area ratios of cementite and MC type carbides were measured using a test piece that had been etched with 3 vol% nital after the observation surface of the outer surface observation test piece had been mirror-polished. The area ratio of cementite was measured by taking metallographic photographs of five arbitrary points of view at 100x magnification, and the area ratios of MC type carbides were measured by taking metallographic photographs of five arbitrary points of view at 500x magnification, and the area ratios of each were calculated by image analysis. The average value of each area ratio was then calculated to be the area ratio of cementite and MC type carbides of the test piece. The calculation of the area ratios of MC type carbides and cementite by image analysis was carried out by the following method. The area ratio of MC type carbides was calculated by measuring the area of white regions with a circle equivalent diameter of 10 μm or less by image analysis and dividing it by the area of the entire observation field. The area ratio of cementite was calculated by measuring the area of white regions with a circle equivalent diameter of 10 μm or less by image analysis and dividing it by the area of the entire observation field. In addition, small white areas of 10 μm or less in the metallographic photograph at 500 times magnification are MC type carbides, and white areas in the metallographic photograph at 100 times magnification are cementite.
[0041] The average grain size of martensite and bainite was measured by EBSD after mirror polishing the observation surface of the outer surface observation specimen. 2The EBSD measurement of the above regions was performed. Using the obtained data, a boundary line was drawn at the location where the orientation difference with the adjacent measurement point was 15° or more, and the region surrounded by the boundary line was treated as one crystal to measure the grain size, and the average value was taken as the average grain size of martensite and bainite. In addition, in the metal structure of the outer layer material for hot rolling rolls of the present invention, the base is martensite and / or bainite. That is, when the base is martensite, the average grain size means the average grain size of martensite. When the base is bainite, the average grain size means the average grain size of bainite. When the base is martensite and bainite, the average grain size means the average grain size of martensite and bainite.
[0042] The hot rolling roll outer layer material of the present invention is manufactured by centrifugal casting and can be used as a ring roll or a sleeve roll as it is, but is particularly suitable for use as an outer layer material for a hot rolling composite roll suitable for hot finish rolling. The hot rolling composite roll of the present invention preferably comprises an outer layer and an inner layer integrated with the outer layer by welding. An intermediate layer may be disposed between the outer layer and the inner layer. That is, instead of the inner layer integrated with the outer layer by welding, an intermediate layer integrated with the outer layer and an inner layer integrated with the intermediate layer by welding may be used. In the present invention, the compositions of the inner layer and the intermediate layer are not particularly limited, but it is preferable that the inner layer is made of spheroidal graphite cast iron (ductile cast iron) and the intermediate layer is made of a high carbon material having C: 1.50 to 3.00 mass%.
[0043] Next, a method for producing the outer layer material for hot rolling roll and the composite roll for hot rolling according to the present invention will be described.
[0044] The outer layer material for hot rolling rolls is manufactured by centrifugal casting. After the inner surface of a mold is covered with a refractory material mainly made of zircon or the like to a thickness of 0.5 to 5.0 mm, the mold is rotated, and a molten metal having the above-mentioned composition of the outer layer material for hot rolling rolls (molten metal for forming the outer layer material) is poured into the mold so as to obtain a predetermined thickness. The centrifugal casting method may be of any type, including a vertical type (rotating shaft is vertical), a horizontal type (rotating shaft is horizontal), or an inclined type (rotating shaft is oblique).
[0045] In the present invention, the time from the completion of the composition adjustment of the molten metal for forming the outer layer material to the start of pouring the molten metal into the mold is limited. That is, in the present invention, after the composition adjustment of the molten metal for forming the outer layer material is completed, the molten metal is started to be poured into the mold within 3 minutes. The outer layer material for a hot rolling roll of the present invention has a limited composition in order to improve wear resistance, and as a result, the composition is such that graphite is difficult to generate. Therefore, in a normal manufacturing method, the amount of graphite generated is insufficient, and seizure resistance is reduced. Therefore, in the present invention, it is necessary to start pouring the molten metal into the mold within 3 minutes after the composition adjustment of the molten metal for forming the outer layer material is completed. Here, the completion of the composition adjustment of the molten metal for forming the outer layer material refers to the time when all raw materials (including an inoculant in the case of inoculation) necessary for the composition adjustment of the molten metal for forming the outer layer material are charged. By starting pouring the molten metal into the mold within 3 minutes after the compositional adjustment of the molten metal for forming the outer layer material is completed, it is possible to obtain a metal structure having a graphite area ratio of 0.5 to 6.0% in the composition of the outer layer material for hot rolling roll specified in the present invention. More preferably, pouring the molten metal into the mold is started within 1 minute after the compositional adjustment of the molten metal for forming the outer layer material is completed.
[0046] When forming an intermediate layer, it is preferable to pour molten metal for forming the intermediate layer (molten metal having the component composition of the intermediate layer) while rotating the mold during or after the outer layer material is completely solidified, and perform centrifugal casting. After the outer layer (or the intermediate layer, if there is an intermediate layer) is completely solidified, the rotation of the mold is stopped, the mold is erected, and the inner layer material is statically cast to form a composite roll. This remelts the inner surface side of the roll outer layer material, and a composite roll is formed in which the outer layer and inner layer, or the outer layer and intermediate layer, or the intermediate layer and inner layer are fused together.
[0047] For the inner layer that is statically cast, it is preferable to use spheroidal graphite cast iron, worm-shaped graphite cast iron (CV cast iron), or the like, which has excellent castability and mechanical properties.
[0048] In addition, when an intermediate layer is formed, it is preferable to use graphite steel, high carbon steel, hypoeutectic cast iron, etc. as the intermediate layer material. The intermediate layer and the outer layer are integrally welded, and the outer layer components are mixed into the intermediate layer. From the viewpoint of suppressing the amount of the outer layer components mixed into the inner layer, it is preferable to reduce the amount of the outer layer components mixed into the intermediate layer as much as possible.
[0049] As described above, a composite roll for hot rolling can be obtained in which the outer layer is made of the outer layer material for hot rolling roll of the present invention and which has a three-layer structure of an outer layer, an intermediate layer and an inner layer, or a two-layer structure of an outer layer and an inner layer.
[0050] The outer layer material for hot rolling roll and the composite roll for hot rolling of the present invention are preferably subjected to a heat treatment after casting. The heat treatment is preferably carried out by removing the roll from the mold after casting, heating and holding the roll at 400 to 550°C, and then slowly cooling the roll.
[0051] The preferred hardness of the hot rolling roll outer layer material and hot rolling composite roll of the present invention is 74 to 88 HS (Shore hardness). When the hardness is 74 HS or more, the wear resistance is easily improved. When the hardness is 88 HS or less, the crack resistance is easily improved. A more preferred hardness is 76 HS or more. Also, a more preferred hardness is 86 HS or less. Such a hardness can be obtained by adjusting the heat treatment temperature. The hardness can be measured by the method described in the Examples. EXAMPLES
[0052] The molten metal (molten metal for forming the outer layer material) having the composition shown in Table 1 to which the inoculant was added after melting in a high-frequency melting furnace and heating to 1420°C was then added. After the addition of the inoculant was completed, the molten metal was supplied to a mold of a horizontal centrifugal casting machine under the casting conditions shown in Table 2. As a result, a sleeve roll (corresponding to the outer layer material for hot rolling rolls) with an outer diameter of 250 mm, an inner diameter of 150 mm, and a depth of 70 mm was cast. Note that before supplying the molten metal for forming the outer layer material to the mold to cast the sleeve roll, the inner surface of the mold was coated with a zircon-based refractory material to a thickness of 1.0 mm. After casting, the sleeve roll was heated at 410°C for 10 hours and then slowly cooled, and various test pieces were taken. Note that the symbol "-" in Table 1 indicates that the element was not intentionally added, and includes not only the case where the element is not contained, but also the case where the element is inevitably contained. In addition, the "time (min) until pouring into the mold begins" in Table 2 indicates the time (min) from the time when all the raw materials necessary for adjusting the composition of the molten metal for forming the outer layer material have been added, that is, in this embodiment, the time when the addition of the inoculant has been completed, until pouring of the molten metal into the mold begins.
[0053] Test material Nos. 1 to 15, 40, and 41 shown in Table 1 are examples of the present invention, and test material Nos. 16 to 38 are comparative examples. Note that test material No. 39 is a conventional example.
[0054] In order to evaluate the area ratio of graphite, cementite, and MC type carbide, a structure observation was carried out. The outer surface of the sleeve roll was cut by cutting to reduce the outer diameter from 250 mm to 240 mm, and then, as shown in FIG. 1, a test piece 2 for observing the outer surface was taken from the outer surface side of the cut sleeve roll 1. The size of the test piece was 20 mm x 10 mm x 5 mm (20 mm is the depth direction of the sleeve roll, 10 mm is the circumferential direction of the sleeve roll, and 5 mm is the radial direction of the sleeve roll). The 20 mm x 10 mm surface of the test piece was used as the observation surface (i.e., the observation surface was a position 10 mm inside from the outer surface of the sleeve roll in the thickness direction), and after the observation surface was mirror-polished, metal structure photographs of five visual fields were taken at 100 times magnification with an optical microscope. The area ratio of graphite was measured by image analysis based on the obtained metal structure photograph, and the average value of the five visual fields was calculated to be the graphite area ratio of the test piece. The area ratios of cementite and MC type carbide were measured by the same method as the measurement method described above. The average grain size of martensite and bainite was obtained by EBSD measurement. After mirror polishing the observation surface of the outer surface observation test piece 2, the specimen was subjected to EBSD measurement at an accelerating voltage of 15 kV and a step size of 0.1 μm for 10,000 μm. 2 EBSD measurements were performed on the above regions. Using the data obtained, boundaries were drawn where the orientation difference between adjacent measurement points was 15° or more, and the regions enclosed by the boundaries were treated as one crystal, and the grain size was measured, and the average value was taken as the average grain size of martensite and bainite. In order to accurately evaluate the grain size of martensite and bainite, when performing the EBSD measurements, the measurement software was set to only measure BCC (body-centered cubic) crystal structures.
[0055] The Shore hardness (HS) was measured as follows. For the test pieces for outer surface observation, the Vickers hardness HV50 was measured using a Vickers hardness tester (test force: 50 kgf (490 N)) in accordance with the provisions of JIS Z 2244 (2020). The converted Shore hardness VHS (HS) was calculated using the conversion formula of JIS B 7731 (2000). There were 10 measurement points, and the average value of the 8 points was calculated after removing the highest and lowest values, which was used as the hardness of the test material.
[0056] A wear test was carried out to evaluate the wear resistance. As shown in FIG. 2, a wear test piece 3 (outer diameter 60 mm, thickness 10 mm, chamfered) was taken from the outer surface side of the sleeve roll 1 machined in the same manner as above. The wear test was carried out by a two-disk sliding rolling method between the wear test piece and a mating piece, as shown in FIG. 3. The wear test piece 3 was rotated at 700 rpm while being cooled with cooling water 4. Then, the mating piece 6 (material: S45C, outer diameter: 190 mm, width: 15 mm, C1 chamfered) whose outer surface was heated to 800°C by a high-frequency induction heating coil 5 was brought into contact with the rotating wear test piece 3 with a load of 980 N and rolled at a slip ratio of 9%. The wear test was carried out for 300 minutes, and the mating piece was replaced with a new one every 50 minutes. The wear test was carried out in the same manner as above using a test piece (reference piece) taken in the same manner as above from the sleeve roll of the conventional example. The wear amount of the standard specimen was used as a standard, and the ratio of the wear amount of each test specimen to the standard was calculated as the wear ratio (= (wear amount of standard specimen) / (wear amount of each test specimen)) to evaluate the wear resistance. In this evaluation, a wear ratio of 1.10 or more was determined to be extremely excellent in wear resistance.
[0057] In order to evaluate the seizure resistance, a seizure test was carried out using a drop-weight frictional thermal shock tester shown in FIG. 4. As shown in FIG. 5, a test piece (seizure test piece) 10 of 30 mm×25 mm×20 mm was taken from the outer surface side of the sleeve roll 1 cut in the same manner as above. Note that 30 mm is the circumferential direction of the sleeve roll, 25 mm is the depth direction of the sleeve roll, and 20 mm is the radial direction of the sleeve roll. As shown in FIG. 4, the drop-weight frictional thermal shock tester drops a weight 8 on a rack 7 to rotate a pinion 9, and rubs a mating piece 11 (material: mild steel) against the 30 mm×25 mm surface of the test piece 10. The seizure resistance was evaluated by the area of the mating piece that was seized on the surface of the test piece 10. FIG. 6 shows a schematic diagram of an evaluation method for seizure resistance (seizure area ratio of the seizure test piece). When the mating piece 11 is rubbed against the surface of the test piece 10, the surface temperature of the test piece 10 rises due to frictional heat, and a very thin oxide film is formed on the surface of the test piece, giving it a colored appearance called temper color. The combined area of the colored part (temper color part 12) and the part where the mating piece is burned (burned part 13) is the part where the mating piece is rubbed, and the seizure area ratio was calculated from the area of these parts using the following formula: Seizure area ratio (%) = (area of seizure part 13) / ((area of temper color part 12) + (area of seizure part 13)) x 100. The seizure area ratio obtained when a seizure test was performed on a test piece taken from a conventional sleeve roll in the same manner as above was used as the standard, and test pieces with a seizure area ratio below the standard were judged to have good seizure resistance.
[0058] A thermal shock test was conducted to evaluate crack resistance. As shown in FIG. 7, two test pieces (thermal shock test pieces) 14 of 40 mm×30 mm×20 mm were taken from the outer surface side of the sleeve roll 1 cut in the same manner as above. 40 mm is the circumferential direction of the sleeve roll, 30 mm is the depth direction of the sleeve roll, and 20 mm is the radial direction of the sleeve roll. The thermal shock test was conducted by heating the test piece at 500° C. for 30 minutes, and then putting the test piece into water at 0° C. After the temperature of the test piece dropped to 100° C. or less, it was taken out of the water and cut at the center of the test piece (cutting the 40 mm length into a 20 mm length). Thereafter, the cut surface was mirror-polished and observed with an optical microscope at a magnification of 50 times, and the maximum crack depth H observed in each cut test piece was measured, and the average value was taken as the crack depth of the test piece. A thermal shock test was conducted in the same manner as above using a test piece (reference piece) taken in the same manner as above from the sleeve roll of the conventional example. The crack depth of the reference piece obtained at that time was used as a reference, and the ratio of the crack depth of each test piece to the reference was calculated as the crack depth ratio (= (crack depth of reference piece) / (crack depth of each test piece)) to evaluate the crack resistance. In this evaluation, a crack depth ratio of 1.00 or more was determined to be good in terms of crack resistance.
[0059] Based on the evaluation of the abrasion resistance, seizure resistance and crack resistance, an overall evaluation was made. Those with extremely excellent abrasion resistance (wear ratio ≧ 1.10) and good seizure resistance and crack resistance (seizure area rate below the standard, crack depth below the standard) were marked with ○, and others were marked with ×. Only ○ was considered to be pass.
[0060] [Table 1]
[0061] [Table 2]
[0062] It is clear that the examples of the present invention have good seizure resistance and crack resistance, and also have remarkably excellent wear resistance.
[0063] Therefore, according to the present invention, it is possible to manufacture a hot rolling roll outer layer material and a hot rolling composite roll that are extremely excellent in wear resistance and also have good seizure resistance and crack resistance, and as a result, it is possible to achieve an effect of improving the life of the rolling roll and the productivity of hot rolling. [Explanation of symbols]
[0064] 1 Sleeve roll (sleeve roll machined for evaluation purposes) 2. Test piece for observing outer surface 3. Wear test specimen 4 Cooling water 5 High frequency induction heating coil 6 Counterpart 7. Rack 8 weight 9 Pinion 10 Test piece (seizure test piece) 11 Counterpart 12 Temper Color Section 13 Burned part 14 Test piece (thermal shock test piece) 15. Crack
Claims
1. In mass percent, C: 2.50-4.00%, Si: 0.60-2.50%, Mn: 0.50-4.00%, Cr: 0.50-3.50%, Ni: 1.50-4.40%, V: 1.00-2.50%, Nb: 0.10 to 0.75%, and Mo: 0.30 to 1.50% and the balance being Fe and unavoidable impurities; A roll outer layer material for hot rolling, the Mn and Ni contents of which satisfy the following formula (1), and the Si and V contents of which satisfy the following formula (2): 0.20≦Mn / Ni≦0.80 ... (1) 0.55≦Si / V≦1.85 ... (2) Here, each element symbol in formulas (1) and (2) indicates the content (mass %) of the corresponding element.
2. The composition further includes, in mass%, W: 2.0% or less, Co: 1.00% or less, B: 0.1000% or less, Ti: 0.30% or less, and 2. The hot rolling roll outer layer material according to claim 1, further comprising one or more selected from the group consisting of Zr: 0.30% or less.
3. 3. The hot rolling roll outer layer material according to claim 1, having a metal structure in which an area ratio of graphite is 0.5 to 6.0%, an area ratio of cementite is 30 to 55%, an area ratio of MC type carbide is 0.1 to 5.0%, and an average crystal grain size of martensite and bainite is 2.0 to 20.0 μm.
4. A method for producing an outer layer material for a hot rolling roll according to claim 1 or 2, A method for producing an outer layer material for a hot rolling roll, comprising the steps of: starting to pour the molten metal for forming the outer layer material into a mold within 3 minutes after completing the composition adjustment of the molten metal for forming the outer layer material.
5. A method for producing an outer layer material for a hot rolling roll according to claim 3, A method for producing an outer layer material for a hot rolling roll, comprising the steps of: starting to pour the molten metal for forming the outer layer material into a mold within 3 minutes after completing the composition adjustment of the molten metal for forming the outer layer material.
6. A composite roll for hot rolling having a three-layer structure of an outer layer, an intermediate layer, and an inner layer, or a two-layer structure of an outer layer and an inner layer, 3. A composite roll for hot rolling, wherein the outer layer comprises the outer layer material for hot rolling roll according to claim 1 or 2.
7. A composite roll for hot rolling having a three-layer structure of an outer layer, an intermediate layer, and an inner layer, or a two-layer structure of an outer layer and an inner layer, A composite roll for hot rolling, wherein the outer layer is made of the outer layer material for hot rolling roll according to claim 3.
Citation Information
Patent Citations
Centrifugal composite high-nickel-niobium wear-resisting cast iron roll and casting method thereof
CN103074539A
Roll for hot rolling made by centrifugal casting
JP2001279367A
External layer material for composite roll for rolling made by centrifugal casting
JP2008050681A
Rolling compound roll
JP2015193025A
Centrifugal casting hot-rolling compound roll
JP2017185548A